Stability Of Tailings Dams ? Part I: Static Loading - E. Sarris (Society for Mining, Metallurgy & Exploration, 2005)
Tailings dams are large-scale earth-fill embankments that are designed to contain mining wastes from ore dressing plants. Most commonly tailings dams are constructed in stages in order to keep up with the increasing volume of mine tailings. Staged construction using various methods (like up-stream, down-stream, and centerline) is generally considered as a very effective way to construct this kind of embankments. The present study is devoted to the investigation of the behavior and the stability of these geostructures under static conditions. In order to accomplish this task, elaborate two-dimensional numerical models are examined, utilizing the geotechnical finite-element code PLAXIS. Numerical analyses are conducted for all three types of tailings dams in order to obtain the potential modes of failure, while the corresponding factors of safety are determined by the shear strength reduction technique.